POLITICS OF POWER IN MARGINALIZATION OF SASAK GANDRUNG PERFORMING ART IN LOMBOK - Trisnawati, Ida Ayu; Suarka, I Nyoman; Parimartha, I Gde; Sugiartha, I Gede Arya (E-Journal of Cultural Studies, 2016)
A change is occurring to the Sasak gandrung performing art performed at Dasan Tereng Village, Narmada District, West Lombok District, West Nuasa Tenggara. The development of the understanding of Islam among the Sasak ethnic people has widely affected the development of such a performing art. The marginalization of the Sasak gandrung performing art cannot be separated from the limited protection given by the government, the strengthening of the religious fundamentalism, and the decrease in the supporting community’s self-confidence.  This present study is intended to identify one of the three phenomena of the marginalization of the gandrung Sasak performing art, especially the strengthening of the religious fundamentalism of the waktu lima Islam. The data were collected through observation, interview, and documents which are related to the gandrung Sasak. The data were analyzed qualitatively using the Theory of Social Practice proposed by Pierre Bourdieu. The results of the study show that the strengthening of the religious fundamentalism of waktu lima Islam caused the wetu telu Muslims to convert into waktu lima Muslims. The consequence is that the gandrung Sasak performing art, inherited from generation to generation, has gradually become marginalized. It has not been included in the list of the performing art in West Lombok Regency. The strengthening of the religious fundalism cannot be separated from the wetu telu Islamic teaching which is not in accordance with the waktu lima Islamic teaching, which is based on Al-Quran and Hadist.  Such a gandrung performing art is believed to be not in accordance with Al-Quran and Hadist which are believed by the waktu lima Muslims.